Pemberdayaan Pokdarwis dalam Mengembangkan Homestay di Desa Bukit Bamba Kecamatan Kahayan Tengah Kabupaten Pulang Pisau (Neolectura, 2020)
This service aims to provide assistance to members of the Rasau Hapakat tourism awareness group in Bukit Bamba Village, Kahayan Tengah District, Pulang Pisau Regency regarding ecotourism management, especially developing the potential of homestays to complement tourism facilities in the village. This service begins with social analysis which is then continued with the appreciative inquiry method. which includes the discover, dream, design, and destiny stages as well as the PRA (participatory rural appraisal) approach. The target of this service is a member of the Rasau Hapakat tourism awareness group (Pokdarwis) in Bukit Bamba Village who is actively involved in the management of a tourism village. Tourism awareness groups are given training, outreach, mentoring, and empowerment regarding ecotourism management. The results of this service show the very good motivation of the tourism conscious group in planning the management and development of the homestay, through the fulfillment of facilities according to the needs, maintenance and promotion in order to empower the economy of the community around tourist attractions.